ANALISIS DAYA TAHAN MAHASISWA DALAM MELANJUTKAN STUDI DENGAN CHI-SQUARED AUTOMATATIC INTERACTION DETECTION - KURNIA, LELY (Sainstek : Jurnal Sains dan Teknologi, 2016)
This research studies the stuctural interaction between variables that become characteristics or factors affecting durability for students to continue their studies. In this study, the data used are the characteristics of students in the form of data counting and categories so that statistical methods used was CHAID analysis. Dendogram CHAID showed that the variables having strongest association with the durability for students to continue their studies is the mark of Calculus I subject. CHAID method to the analysis of durability for students to continue their studies produced three segments. The first segment is the students who retook the Calculus I subject, the second one is the students who passed or failed in Calculus I subject with semester 1 GPA < 3.00 and the last is the students who passed or failed in Calculus I subject with semester 1 GPA > 3.00. Key words: Chi-Squared Automatatic Interaction Detection Analysis (Chaid), Student